THE LEVANTINE BASIN-CRUSTAL STRUCTURE AND ORIGIN - Netzeband G.L.; Hübscher C.P.; Dehghani G.A.; Gajewski D.; Liersch P.; Gohl K.; Ben-Avraham Z. (My University, 2006)
The origin of the Levantine Basin in the Southeastern Mediterranean Sea is related to the opening of the Neo-Tethys. The nature of its crust has been debated for decades. Therefore, we conducted a geophysical experiment in the Levantine Basin. We recorded two refraction seismic lines with 19 and 20 ocean bottom hydrophones, respectively, and developed velocity models. Additional seismic reflection data yield structural information about the upper layers in the first few kilometers. The crystalline basement in the Levantine Basin consists of two layers with a P-wave velocity of 6.0-6.4 km/s in the upper and 6.5-6.9 km/s in the lower crust. Towards the center of the basin, the Moho depth decreases from 27 to 22 km. Local variations of the velocity gradient can be attributed to previously postulated shear zones like the Pelusium Line, the Damietta-Latakia Line and the Baltim-Hecateus Line. Both layers of the crystalline crust are continuous and no indication for a transition from continental to oceanic crust is observed. These results are confirmed by gravity data. Comparison with other seismic refraction studies in prolongation of our profiles under Israel and Jordan and in the Mediterranean Sea near Greece and Sardinia reveal similarities between the crust in the Levantine Basin and thinned continental crust, which is found in that region. The presence of thinned continental crust under the Levantine Basin is therefore suggested. A β-factor of 2.3-3 is estimated. Based on these findings, we conclude that sea-floor spreading in the Eastern Mediterranean Sea only occurred north of the Eratosthenes Seamount, and the oceanic crust was later subducted at the Cyprus Arc. © 2006 Elsevier B.V. All rights reserved.
Keywords: CRUSTAL STRUCTURE; GRAVITY; LEVANTINE BASIN; REFRACTION SEISMICS